HBR's 10 must reads 2023 - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2022)
"We've combed through the ideas, insights, and best practices from the past year of Harvard Business Review to help you get up to speed fast on the relevant concepts driving business today. Discover new ideas and sample the latest thinking of our vast array of management experts. Revisit these topics now to make sure your organization is incorporating the best, most up-to-date practices, or keep this book as a reference so you can turn to these memorable pieces when you need them the most. The collection includes articles on leadership, diversity, and strategy, as well as articles that will help you manage yourself and others"--
The Future of Flexibility at Work / by Ellen Ernst Kossek, Patricia Gettings, and Kaumudi Misra -- Eliminate Strategic Overload / by Felix Oberholzer-Gee -- Drive Innovation with Better Decision-Making / by Linda A. Hill, Emily Tedards, and Taran Swan -- Unconscious Bias Training that Works / by Francesca Gino and Katherine Coffman -- Why You Aren't Getting More from Your Marketing AI? / by Eva Ascarza, Michael Ross, and Bruce G.S. Hardie -- Net Promoter 3 / by Fred Reichheld, Darci Darnell, and Maureen Burns -- How Chinese Retailers are Reinventing the Customer Journey / by Mark J. Greeven, Katherine Xin, and George S. Yip -- The Circular Business Model / by Atalay Atasu, Céline Dumas, and Luk N. Van Wassenhove -- How to Succeed Quickly in a New Role / by Rob Cross, Greg Pryor, and David Sylvester -- Accounting for Climate Change / by Robert S. Kaplan and Karthik Ramanna -- Persuading the Unpersuadable / by Adam Grant
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Success in business; Industrial management; Industrial management; Success in business